Redução da carga orgânica de efluentes industriais contaminados com óleo, pela ação do reagente de Fenton - Maria Augusta das Dores Silva Fonseca (2007)
The water pollution has increased along all these years, but meanly during the last years with the growth and development of the industrial sector. The oil and its derivatives are classified among the main pollutants of the aquatic environment. As the economy and the industrial activities grow in the world, the consumption of the oil and its derivatives enlarges, generating a large increase in the oil contaminated wastewater. This type of wastewater is characterized by its high organic load (COD) and low biodegradability due to the presence of different organic compounds. The physicochemical treatment of these wastewaters (coagulation/flocculation), used conventionally in industries, is not enough to reduce the organic load in these effluents to a level allowed by the specific legislation. Then, the use of alternative techniques for treating these wastewaters becomes important. This work has aimed for developing a process route to perform the treatment of these oil contaminated wastewaters, by using of Advanced Oxidative Processes through the application of Fentons Reagent. This route should be feasible, economically and technically, to be incorporated into any industrial process, for reducing efficaciously the organic load (Chemical Oxygen Demand) in this effluent type. Experiments performed in this work have been used a standard oil contaminated wastewater, made in laboratory, with its chemical composition defined and controlled to well represent a tipic industrial wastewater contaminated with emulsified oils. Preliminary results have shown that the application of Fentons reagent directly on this effluent is not efficient, since the oily emulsion breakage cannot be even reached. Based on these results, a conjugate technique has been proposed, consisting of the following route: the conventional treatment beginning with the oil emulsion breakage; the treatment with Fentons reagent and a final step involving flocculation. This proposal was tested performing a new set of experiments, which have confirmed that this route of combined techniques presents better results than those obtained in the conventional physicochemical treatment. The operational range, recommended for obtaining the COD value within the limit allowed by the technical norm T 187.2 from COPASA (COD < 450 mg/L), is specified as: 750 to 1.250 mg/L for the hydrogen peroxide concentration; 300 to 500 mg/L for the iron concentration and 120 e 240 minutes for the reaction time. An analysis of costs required to operate industrially this new route was performed for comparing to the costs expend in the conventional treatment of this wastewater. This comparison confirmed the feasibility of implement this new route into the industry, since difference between these two costs was not significant. However, as shown, the restricted variable for implementing this new route in any industry is, in fact, the reaction time, which increases in one hour the time of the conventional treatment. For the industry analyzed in this work, the time increase in the treatment implies in operating the effluent treatment work station at its maximum capacity.